False fame effects emerge following an internal context shift and are abolished with contextual reinstatement. Issue 8 (14th September 2019) - Buchli, Dorothy R.
ABSTRACT: Prior research has demonstrated that if you give people a list of nonfamous names and ask them to indicate if the names are famous, 24 hours later, more of these names will be incorrectly remembered as famous than without the delay. This is because while participants are no longer able to recall the specific circumstances in which they previously encountered the names, the names remain familiar and this sense of familiarity is falsely attributed to fame. The present study sought to determine whether a false fame effect would emerge if a daydreaming task, designed to shift participants' internal context, was interpolated between a list of nonfamous names and a list of famous names. Results revealed that indeed, participants erroneously judged more nonfamous names as famous following an internal Context Change. This effect was abolished, however, when the initial context (in which the nonfamous list was studied) was reinstated. Therefore, a contextual-change account of the phenomenon may be appropriate.